Konstruksi Yuridis Ganti Kerugian Perdata Akibat Pelanggaran Data Pribadi (Doxing) Berdasarkan Pasal 12 UndangUndang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi dalam Perspektif Perbuatan Melawan Hukum - Nazwa Rahmannina Rustandi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The practice of doxing, in the form of disclosing personal data without a lawful basis, may cause non-material harm to victims, while the parameters for compensation under Law Number 27 of 2022 concerning Personal Data Protection remain inadequately regulated. This study is relevant because an initial legal basis is needed for victims of personal data violations to seek remedies through Indonesian civil law mechanisms. This article constitutes normative legal research employing statutory, conceptual and comparative approaches. The study aims to analyze the construction of civil liability for doxing perpetrators and to formulate a basic reconstruction of the mechanism for determining non-material damages for victims. The findings show that doxing may be qualified as an unlawful act by positioning Article 12 of the PDP Law as the basis for the right to sue and Article 1365 of the Indonesian Civil Code as the framework for proof. This study also proposes a factor-based assessment model for determining non-material damages, using Article 82 of the General Data Protection Regulation as a principled reference that must be adapted to the Indonesian legal system. In conclusion, this study is not intended to serve as a final guideline for determining damages, but rather as an initial legal basis for doxing victims in constructing civil claims and as a conceptual foundation for developing parameters of non-material damages in Indonesia. The practice of doxing, in the form of disclosing personal data without a lawful basis, may cause non-material harm to victims, while the parameters for compensation under Law Number 27 of 2022 concerning Personal Data Protection remain inadequately regulated. This study is relevant because an initial legal basis is needed for victims of personal data violations to seek remedies through Indonesian civil law mechanisms. This article constitutes normative legal research employing statutory, conceptual and comparative approaches. The study aims to analyze the construction of civil liability for doxing perpetrators and to formulate a basic reconstruction of the mechanism for determining non-material damages for victims. The findings show that doxing may be qualified as an unlawful act by positioning Article 12 of the PDP Law as the basis for the right to sue and Article 1365 of the Indonesian Civil Code as the framework for proof. This study also proposes a factor-based assessment model for determining non-material damages, using Article 82 of the General Data Protection Regulation as a principled reference that must be adapted to the Indonesian legal system. In conclusion, this study is not intended to serve as a final guideline for determining damages, but rather as an initial legal basis for doxing victims in constructing civil claims and as a conceptual foundation for developing parameters of non-material damages in Indonesia.